Genetics of hereditary forms of dystonia - M. Yu. Krasnov; S. L. Timerbaeva; S. N. Illarioshkin (Анналы клинической и экспериментальной неврологии, 2017)
Dystonia is one of the most common movement disorders withgreat medical, social and economic importance. Genetics playssignificant role in the development of different, and mainly primary,forms of dystonia. At present the range of hereditary dystonicsyndromes comprises more than twenty separate clinicalgeneticvariants, which characterizes dystonia as a highly heterogeneousnosologic group calling for differentiated approachesto diagnosis and treatment. Detailed analysis of the literatureon hereditary forms of dystonia, including clinical picture,molecular genetic basis, phenotypegenotype correlations, andprinciples of DNA diagnostics and medical genetic counselingof affected families, is presented.